Αντισεισμική ενίσχυση υφιστάμενης κατασκευής - Σοφοκλέους, Παναγιώτα (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικης, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
The seismic strengthening is one of the most important areas of engineering, especially in countries which are located in seismic regions. A large percentage of existing buildings in Cyprus can not be regarded safe regarding their seismic resistance. Due to recent technological developments, various methods for the assessment and retrofitting of buildings have been developed and a big part of the problem of earthquake resistant construction has been solved. The retrofitting of existing structures prolongs their design life, which results in economic benefits In this thesis, the methodologies to be followed for a proper seismic strengthening are reviewed. In addition, information about available strengthening methods is given. More specifically, in Chapter Οne some principles for the strengthening of structures are listed, including the decision for the selection of the proper strengthening methodology, as well as the classification of faults that appear in buildings. In Chapter Two, some of the strengthening methods are presented together with the advantages and disadvantages of each method. Then, chapters Three, Four, Five and Six follow in which an example of a real building is described that was modeled and strengthened in two different ways: using jackets and reinforced concrete walls. Subsequently, comparisons were made between the two methodologies and the most suitable and more economic method for this building was selected. The results and general observations from the process are presented in Chapter Seven.
Keywords: Seismic Strengthening; Seismic Regions; Structures Strengthening; Αντισεισμική Ενίσχυση; Σεισμογενείς Περιοχές; Ενίσχυση Κατασκευών